2021
DOI: 10.3390/s21227466
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Characteristics of EEG during Active Emotional Musical Performance

Abstract: The research on neural correlates of intentional emotion communication by the music performer is still limited. In this study, we attempted to evaluate EEG patterns recorded from musicians who were instructed to perform a simple piano score while manipulating their manner of play to express specific contrasting emotions and self-rate the emotion they reflected on the scales of arousal and valence. In the emotional playing task, participants were instructed to improvise variations in a manner by which the targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…Their research involved having musicians perform a simple piano piece while adjusting their manner of play to transmit opposing feelings, and self-rating the emotion portrayed on arousal and valence scales. In both distressed and comfortable playing, EEG activity differed [40]. Electroencephalograms (EEGs) are widely used to record brain responses to brief, repeating stimuli.…”
Section: Source Localization Datamentioning
confidence: 99%
“…Their research involved having musicians perform a simple piano piece while adjusting their manner of play to transmit opposing feelings, and self-rating the emotion portrayed on arousal and valence scales. In both distressed and comfortable playing, EEG activity differed [40]. Electroencephalograms (EEGs) are widely used to record brain responses to brief, repeating stimuli.…”
Section: Source Localization Datamentioning
confidence: 99%
“…It has been shown that brain activity during the perception of emotions induced by music-listening differs from that involved in the creative expression of emotion through music performance [ 24 ]; moreover, it is possible that music performers experience different emotions than what they are trying to express through the performance [ 25 ]. In our previous works [ 11 , 12 ], we demonstrated that both power and effective connectivity patterns differ when professional musicians are instructed to play distressed, excited, depressed, relaxed, or neutrally labeled music pieces.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have focused on spectral power measurements as a tool to reveal the brain activity behind emotional experiences elicited by listening to music. Power changes in different frequency bands and over multiple brain areas have been reported to be related to changes in arousal and valence corresponding to different emotional states [ 8 , 9 , 10 , 11 , 12 ]. However, a large information flow between different cortical areas occurs during emotional music processing [ 13 ], and this should be considered when comparing emotions at a neurophysiological level.…”
Section: Introductionmentioning
confidence: 99%
“…The authors contrasted emotional playing with neutral playing to detect patterns of motor and sensory activation related to the emotional aspects of the performance. Pousson et al [56] recorded EEG activity from musicians who were instructed to perform a simple piano score in an emotional way and in a neutral way. In the emotional playing task, participants were instructed to improvise variations in a manner by which the targeted emotion was communicated, while in the neutral playing task, participants were asked to play the same piece precisely as written in the score.…”
Section: Introductionmentioning
confidence: 99%